Brief Report: High Accuracy of a Real-Time Urine Antibody-Based Tenofovir Point-of-Care Test Compared With Laboratory-Based ELISA in Diverse Populations. (1st June 2020) - Spinelli, Matthew A.; Rodrigues, Warren C.; Wang, Guohong; Vincent, Michael; Glidden, David V.; Okochi, Hideaki; Stalter, Randy; Defechereux, Patricia; Deutsch, Madeline; Grant, Robert M.; Ngure, Kenneth; Mugo, Nelly R.; et al.
Abstract : Background: Therapeutic drug monitoring measures antiretroviral adherence more accurately than self-report but has not been available at the point-of-care (POC) until now. We compare a novel POC test for urine tenofovir to laboratory-based enzyme-linked immunosorbent assay (ELISA) testing in diverse patient populations urine pre-exposure prophylaxis (PrEP). Setting: Urine samples were analyzed using ELISA and the POC lateral flow immunoassay (LFA) test from 2 cohorts of PrEP users taking tenofovir disoproxil fumarate/emtricitabine: the Partners PrEP Study, which recruited Kenyan and Ugandan heterosexual men and women, and the IBrEATHe Study, which recruited US transgender women and men using gender-affirming hormone therapy. Methods: We calculated the sensitivity, specificity, and accuracy of the POC test compared with ELISA at a cutoff of 1500 ng/mL. Results: Overall, 684 urine samples were tested from 324 participants in the 2 cohorts. In Partners PrEP, 454 samples from 278 participants (41% women) were tested with a median age of 33 years. In IBrEATHe, 231 samples from 46 individuals (50% transwomen) were tested with a median age of 31 years. Comparison of the LFA read-out to ELISA yielded 100% sensitivity [97.5% one-sided confidence interval (CI) = 99.3%], 98.3% specificity (95% CI = 95.2% to 99.7%), and 99.6% accuracy (95% CI = 98.7% to 99.9%). Conclusion: The sensitivity, specificity, and accuracy of a novel POC test for urine tenofovir all exceeded 98% when compared with a laboratory-based ELISA method when tested in diverse patient populations. Given the LFA's high accuracy and expected low cost, this POC test is a promising tool to support antiretroviral adherence that could be widely scalable to real-world clinical settings.